The Songlines: Bruce Chatwin’s Spiritual Biography - López Hernández, Isabel (2021)
The Songlines could be defined as the spiritual biography of British writer Bruce Chatwin (1940-1989). In this book he reveals his obsessions and he realizes that it is time to explain the root of his restlessness, that unexplainable urge to flee from home. Published two years before his death, he brings to light the ideas he had been nurturing since childhood. The adventure of two men exploring the virgin territory of Australia reaped enormous critical and public success. He found in the aboriginal creation myth a representation of his concern on nomadism. He wrote about people who create their world in motion. In order to analyze how the author incorporates all these ideas, the first section of the present article examines the origin of his interest in nomadism and Australia. Secondly, it deepens on how the aboriginal philosophy helps him explain his own nomadic urge. Finally, the article considers the chapter titled From the Notebooks, because it constitutes the backbone of his personal philosophy.